Pengaruh Budaya Organisasi terhadap Kinerja Karyawan di Perusahaan Startup - Eloh Bahiroh; Desty Alvi Noor Agustina (Lembaga Pengembangan Kinerja Dosen, 2025)
In the competitive business world, organizational culture is a key factor affecting employee performance, especially in startup companies that often face challenges in growth and innovation. This study aims to analyze the influence of organizational culture on employee performance in startup companies, focusing on elements such as communication, collaboration, and managerial support. A strong organizational culture is believed to increase employee motivation and productivity, which in turn will contribute to the company's success. The results show that a positive organizational culture, including collaborative, innovative, and open values, contributes significantly to increased employee motivation and productivity. Employees who engage in a positive organizational culture tend to be more productive and have a higher retention rate because they feel supported by their company. The practical implication of this study is that startup companies need to actively create and build a productive work atmosphere to increase employee motivation.